Activation of cytokine responses by Candida africana. (4th October 2022) - Rosati, Diletta; Bruno, Mariolina; van de Veerdonk, Frank; ten Oever, Jaap; Meis, Jacques F; Netea, Mihai G
Abstract: Candida africana is a fungal pathogen that rarely causes invasive infections, but is mainly isolated from patients with vaginal infections. Vulvovaginal candidiasis is associated with dysregulated inflammatory responses of the host, however, the innate immune responses against C. africana are currently unknown. In this study, we explored the cytokine production of human peripheral blood mononuclear cells (PBMCs) in response to different C. africana isolates (intra-species diversity), and compared it with that induced by other yeasts belonging to the C. albicans species complex such as C. dubliniensis and C. albicans. Candida africana isolates induced both pro- and anti-inflammatory cytokines broadly similar to other Candida species. Candida africana -stimulated PBMCs tended to produce lower Interleukin (IL)-17 and IL-22 levels in comparison with C. albicans, whereas the induction of trained immunity was similar between C. africana and other Candida species. Overall, our results demonstrate that C. africana induces similar innate immune responses as the other Candida species. Therefore, its propensity to cause vulvovaginal infections is not due to an increased capacity to induce cytokine-related immune pathology. Nor is the infrequent occurrence of invasive infection by C. africana explained by a quantitatively different cytokine induction. Lay Summary: Candida africana has been reported to cause vulvovaginal candidiasis. This study shows that C. africana induces broadly similar cytokine production and trained immunity as other Candida species. Its propensity to cause vaginal infections is not due to an enhanced capacity to cause immune dysregulation.